Intracardiac vs. transesophageal echocardiography for guiding transcatheter closure of interatrial communications: a systematic review and meta-analysis - Lan, Qingsu; Wu, Fengchao; Ye, Xudong; Wang, Shaohua; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2023)
Background Transcatheter closure of atrial septal defect (ASD) and patent foramen ovale (PFO) is an established practice, and it requires monitoring and guidance. Both transoesophageal echocardiography (TEE) and intracardiac echocardiography (ICE) can be used as guidance tools. However, the use of ICE and TEE in structural heart disease is controversial and the advantages and disadvantages of both for ASD and PFO closure need to be investigated. We did a systematic review and meta-analysis to compare the efficacy and safety of TEE and ICE for guiding transcatheter closure of ASD and PFO. Methods A systematic search of Embase, PubMed, Cochrane library, Web of Science was conducted from inception to May 2022. The outcomes of this study included average time for both fluoroscopy and the procedure, complete closure, length of stay at hospital and adverse events. This study was performed using mean difference (MD), relative risk (RR) and 95% confidence interval (CI). Results The meta-analysis was conducted with a total of 11 studies, involving 4,748 patients were included in meta-analysis, including 2,386 patients in the ICE group and 2,362 patients in the TEE group. The results of the meta-analysis showed that compared with TEE, ICE was shorter in time both fluoroscopy [MD: −3.72 (95%CI: −4.09 to −3.34) minutes, P < 0.00001] and the procedure [MD: −6.43 (95%CI: −7.65 to −5.21) minutes, P < 0.00001], shorter length of stay at hospital [MD = −0.95 (95% CI = −1.21 to −0.69) days, P < 0.00001], lower incidence of adverse events (RR = 0.72, 95%CI: 0.62 to 0.84, P < 0.0001), and the arrhythmia (RR = 0.50, 95% CI = 0.27 to 0.94, P = 0.03) and vascular complications (RR = 0.52, 95%CI = 0.29 to 0.92, P = 0.02) in ICE group were lower than those in TEE group. No significant difference in complete closure was found between ICE and TEE (RR = 1.00, 95% CI = 0.98 to 1.03, P = 0.74). Conclusion Under the premise of ensuring successful rate of complete closure, ICE can shorten time between fluoroscopy and procedure and length of stay at hospital, and there was no increase in adverse events. However, more high-quality studies are needed to confirm the benefits of using ICE in ASD and PFO closure.